2006
DOI: 10.1007/s10433-006-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between work-status and leisure lifestyle at the age of 60 years old

Abstract: The tendency to leave work before the formal pension age is reached has increased in most OECDcountries. The societal economical consequences of these circumstances are worrying and knowledge about the mechanisms behind this trend is urgent. Previous research has focused on the role of pension rules, work environments, health and education. In this study, it was investigated if there are differences in personality and in leisure lifestyle between individuals who have retired at the age of 60 and individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…So far there have been very few studies investigating positive relationships between quality of life in its ED and physical activity. Some authors point to higher levels of physical activity among individuals with enough leisure time or with sufficient material resources 62 as components of quality of life in its ED. An earlier study by one of the authors of the present work 63 showed that having leisure and taking advantage of leisure opportunities constitute one of the most important determinants of quality of modern life.…”
Section: Discussionmentioning
confidence: 99%
“…So far there have been very few studies investigating positive relationships between quality of life in its ED and physical activity. Some authors point to higher levels of physical activity among individuals with enough leisure time or with sufficient material resources 62 as components of quality of life in its ED. An earlier study by one of the authors of the present work 63 showed that having leisure and taking advantage of leisure opportunities constitute one of the most important determinants of quality of modern life.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire, which previously has been used in the Swedish version used here (Rennemark and Berggren 2006), consists of 60 items that describe personality traits. A Likertscale with steps from 1 (do not agree at all) to 5 (agree completely) was used.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, people may want to retire to take care of a needy family member or, alternatively, to continue working to provide the necessary resources for covering medical expenses (Talaga & Beehr, 1995). Conversely, people may wish to retire to spend more time with a spouse when his or her health condition is good (e.g., Floyd & Haynes, 1992;Rennemark & Berggren, 2006). Perceived personal health and spouse health status were, thus, used as controls in this study.…”
Section: Control Variablesmentioning
confidence: 98%